Sintesis Katalis Platina-Titanium Dioksida Dengan Substitusi Reduced Graphene Oxide Dan Karakterisasinya Menggunakan Pengujian Cyclic Voltammetry - Jaya, B. Gde Edy Triana Adi; Joni, Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstract The increased use of fossil fuels as an energy source has become a major cause of crises and pollution. Some renewable energies are being developed, such as hydrogen, which can be applied in Proton Exchange Membrane Fuel Cells (PEMFC). PEMFC is a device that converts hydrogen into electrical energy through a key component known as the Membrane Electrode Assembly (MEA). The MEA includes a catalyst where the reduction-oxidation reactions occur. Pt/C catalysts are commonly used as electrocatalysts, but their scarcity, high cost, and susceptibility to corrosion are significant drawbacks. The addition of supporting materials such as TiO2 and rGO can enhance the performance of Pt catalysts. Therefore, the synthesis of Pt.TiO2/rGO catalysts with specific mass variations and several advanced methods including modified Hummers, hydrothermal, and photodeposition were performed to obtain cost-effective catalysts. The characterization of the catalysts was conducted using Cyclic Voltammetry (CV) to determine the conductivity characteristics of voltage-current in the reduction-oxidation reactions on the Pt.TiO2/rGO catalyst. The results showed that the catalyst with the highest Pt mass variation exhibited the anodic peak potential for the oxidation reaction and produced a current of 1.1 mV. Keywords: PEMFC, Catalyst, Pt.TiO2/rGO, Cyclic voltammetry